f(0) = 2×2 + 45 – 5 g(2) = 623 – 2x² +3 Find (f +9)(2) A. (f +9)(2) = -6213 + 4×2 + 42 – 8 B. (f +g)(x) = 623 + 47 –

Question

f(0) = 2×2 + 45 – 5
g(2) = 623 – 2x² +3
Find (f +9)(2)
A. (f +9)(2) = -6213 + 4×2 + 42 – 8
B. (f +g)(x) = 623 + 47 – 2
c. (f +9)(2) = 6203 – 202 + 4x – 2
D. (f +9)(x) = 8.23 + 2x – 2

in progress 0
Trung Dũng 2 months 2021-07-21T18:26:45+00:00 1 Answers 1 views 0

Answers ( )

    0
    2021-07-21T18:28:31+00:00

    Answer:

    hello there i think answer is B

    Step-by-step explanation:

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )